Marion Jones sprinting sensation - Stewart, Mark (New York Children's Press, 1999)
A biography of the young woman who excelled at both basketball and track at the University of North Carolina, but has focused on running and long jump events since 1997
American Corner
11
Keywords: Jones, Marion -- 1975- -- Juvenile literature; African Americans -- Biography; Basketball players -- United States -- Biography -- Juvenile literature; Basketball players; Runners (Sports) -- United States -- Biography -- Juvenile literature; Track and field athletes -- United States -- Biography -- Juvenile literature; Women -- Biography